Production of ethanol and xylanolytic enzymes by yeasts inhabiting rotting wood isolated in sugarcane bagasse hydrolysate. Issue 7 (July 2020) - Morais, Camila G.; Sena, Letícia M.F.; Lopes, Mariana R.; Santos, Ana Raquel O.; Barros, Katharina O.; Alves, Camila R.; Uetanabaro, Ana Paula T.; Lachance, Marc-André; Rosa, Carlos A.
Abstract: Yeasts associated with rotting wood from four Atlantic Rain forest sites in Brazil were investigated using a culture medium based on sugarcane bagasse hydrolysate. A total of 330 yeast strains were isolated. Pichia manshurica, Candida pseudolambica, and Wickerhamomyces sp. 3 were the most frequently isolated species. Fourteen novel species were obtained in this study. All isolates were tested for their ability to ferment d -xylose and to produce xylanases. In the fermentation assays using d -xylose (30 g L −1 ), the main ethanol producers were Scheffersomyces stipitis (14.08 g L −1 ), Scheffersomyces sp. (7.94 g L −1 ) and Spathaspora boniae (7.16 g L −1 ). Sc. stipitis showed the highest ethanol yield (0.42 g g −1 ) and the highest productivity (0.39 g L −1 h −1 ). The fermentation results using hemicellulosic hydrolysate showed that Sc. stipitis was the best ethanol producer, achieving a yield of 0.32 g g −1, while Sp. boniae and Scheffersomyces sp. were excellent xylitol producers. The best xylanase-producing yeasts at 50 °C belonged to the species Su. xylanicola (0.487 U mg −1 ) and Saitozyma podzolica (0.384 U mg −1 ). The results showed that rotting wood collected from the Atlantic Rainforest is a valuable source of yeasts able to grow in sugarcane bagasse hydrolysate, including species with promising biotechnological properties. Highlights: Sugarcane bagasse hydrolysate medium was used for yeast isolation from rotting wood. 330 strains were isolated and identified as 66 known species and 14 novel yeast species. Scheffersomyces stipitis was the best ethanol producer in bagasse hydrolysate medium. Spathaspora boniae and Scheffersomyces sp. were excellent xylitol producers. The best xylanase-producing species were Su. xylanicola, Saitozyma podzolica and A. sporotrichoides.